At first we should know that:
" The sum of the lengths of two sides of a triangle must be grater than the length of the length of the third side "
which mean:
For a triangle ABC :
AB + BC > AC
& AB + AC > BC
& AC + BC > AB
Applying the theorem to the problem:
we have AB = 12 cm. and BC = 10 cm.
For option (a): if AC = 2 cm. ⇒⇒⇒ AC + BC = 10 + 2 = 12 = AB
So option (a) ⇒ could not be the length of AC
For option (b): if AC = 3 cm. ⇒⇒⇒ AB + BC = 12 + 10 = 22 > AC
& AB + AC = 12 + 3 = 15 > BC
& AC + BC = 3 + 10 = 13 > AB
So option (b) ⇒ could be the length of AC
For option (c): if AC = 8 cm. ⇒⇒⇒ AB + BC = 12 + 10 = 22 > AC
& AB + AC = 12 + 8 = 20 > BC
& AC + BC = 8 + 10 = 18 > AB
So option (c) ⇒ could be the length of AC
For option (d): if AC = 16 cm. ⇒⇒⇒ AB + BC = 12 + 10 = 22 > AC
& AB + AC = 12 + 16 = 28 > BC
& AC + BC = 16 + 10 = 26 > AB
So option (d) ⇒ could be the length of AC
For option (e): if AC = 22 cm. ⇒⇒⇒ AB + BC = 10 + 12 = 22 = AC
So option (e) ⇒ could not be the length of AC
For option (f): if AC = 25 cm. ⇒⇒⇒ AB + BC = 12 + 10 = 22 < AC
So option (f) ⇒ could not be the length of AC
The measurements that could be the length of AC are 3 , 8 , 16
i.e.: options (b),(c) and (d)